2018
DOI: 10.1074/jbc.ra118.001858
|View full text |Cite
|
Sign up to set email alerts
|

miR-27a-3p protects against blood–brain barrier disruption and brain injury after intracerebral hemorrhage by targeting endothelial aquaporin-11

Abstract: Previous studies have reported that miR-27a-3p is down-regulated in the serum of patients with intracerebral hemorrhage (ICH), but the implication of miR-27a-3p down-regulation in post-ICH complications remains elusive. Here we verified miR-27a-3p levels in the serum of ICH patients by real-time PCR and observed that miR-27a-3p is also significantly reduced in the serum of these patients. We then further investigated the effect of miR-27a-3p on post-ICH complications by intraventricular administration of a miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(79 citation statements)
references
References 40 publications
(38 reference statements)
5
67
0
Order By: Relevance
“…In this respect, although most of the knowledge concerning the role of AQP1 and AQP4 on the CSF homeostasis has been obtained in animal models, during recent years, growing studies indicate that these AQPs might have similar functions in humans, and their alterations would been implicated in different pathophysiological conditions [7,15,42,43]. Moreover, in the last years, another AQP, AQP11, has been reported to be expressed in the brain [44,45]. Further experimental work should be performed to address if some of the modifications observed in the double-AQP −/− KO could be related with compensation of other AQPs and/or alterations in the brain water content.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, although most of the knowledge concerning the role of AQP1 and AQP4 on the CSF homeostasis has been obtained in animal models, during recent years, growing studies indicate that these AQPs might have similar functions in humans, and their alterations would been implicated in different pathophysiological conditions [7,15,42,43]. Moreover, in the last years, another AQP, AQP11, has been reported to be expressed in the brain [44,45]. Further experimental work should be performed to address if some of the modifications observed in the double-AQP −/− KO could be related with compensation of other AQPs and/or alterations in the brain water content.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that these candidate miRNAs could facilitate neuron survival by regulating expression of genes that have induction of transcription in response to injury. For example, MiR-27a-3p can protect against blood-brain barrier disruption and brain injury by modulating expression of endothelial aquaporin-11 18 . Meanwhile microRNA-27a can suppress expression of the Apaf-1 protein to mitigate hypoxia-induced neuronal apoptosis 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the important role of small RNA in the molecular mechanisms that control the function of the BBB [182]. For example, the microRNA miR-27a-3p was identified in intracerebral hemorrhage patients to regulate BBB function and edema formation via up-regulation of AQP11 [183]. Therefore, small RNA sequencing is an important tool to better understand the role of small RNAs in the BBB.…”
Section: Design and Preparation Of Sequencing Librariesmentioning
confidence: 99%